Profil Keterampilan Menggambar Segi Banyak Siswa Madrasah Ibtidaiyah - Nur Laili Anggun Rahmawati; Ismail Marzuki; Nataria Wahyuning Subayani (Prodi Pendidikan Guru Sekolah Dasar, 2025)
This research aims to understanding students to draw polygons, to identify characteristics of students in drawing polygons, and assess their creativity in drawing polygons. This type of research used a case study research conducted at Madrasah Ibtidaiyah YKUI Sekargadung Dukun Gresik. The subjects of this study were grade 5 with 6 students 3 male students and 3 students. female students. The data collection techniques in this study were observation, interviews, and test questions. Based on the research results, the characteristics of male students are different from the characteristics of female students. Male students tend to be more lively and discuss when working on the test questions given by the researcher. While female students tend to be quieter when working on the test questions given, although there are also female students who work on the test questions by discussing. The creativity of students in drawing polygons has the same results. All students experience misconceptions in drawing pentagonal plane shapes. Of all the research subjects, students draw with one choice between symmetrical and asymmetrical images. In the symmetrical plane shape drawing, male students tend to be able to correctly draw two plane shapes, namely triangles and quadrilaterals. Female students can correctly draw three plane shapes, namely triangles, quadrilaterals and octagons. While in asymmetrical plane shapes, male students can draw two plane shapes, namely triangles and decagons. Female students can draw three plane shapes, namely triangles, ninetagons and decagons. Based on the results of this study, it is recommended that teachers introduce various polygonal plane shapes from an early age. This aims to ensure that students have thoughts or imagination in recognizing and drawing polygonal plane shapes that develop from an early age.